Expressão de fatores relacionados à morte celular programada em embriões bovinos infectados com BHV-5 - Silva-Frade, Camila [UNESP] (2013)
It is known that some pathogens can initiate apoptosis in certain cells of the organism, however, BHV-5 inhibits apoptosis in bovine embryos after seven days of development. Therefore, the aim was to investigate the interaction virus-embryo in the mechanism of programmed cell death. Bovine oocytes were divided into two groups: I (control) and II (exposed to BHV-5). After 24 hours of in vitro maturation, 100 oocytes of each group were denuded and observed under inverted microscope to check the extrusion of the first polar body, and the other oocytes were incubated with spermatozoa for 18 to 20 hours, for in vitro fertilization. After this period, presumptive zygotes were denuded and transferred to drops containing culture medium (mSOF), until day seven postfertilization. In vitro produced embryos were submitted to real time PCR to evaluated the presence of BHV-5 and expression of Mcl-1, Bax, caspase-2, -3 and Apaf-1 related to apoptosis, also the MTT assay ((3 - [4,5-dimethylthiazol 2-yl] -2,5-diphenyl tetrazolium bromide)) was performed for the evaluation of mitochondrial activity. Statistical analysis for nuclear maturation of oocytes was performed by x2 test. In vitro embryo production, MTT and gene expression were analyzed by unpaired t test. It was observed that BHV-5 did not influence nuclear maturation rate of oocytes or embryonic development, however embryos of group I showed greater mitochondrial viability, and embryos of group II had a decrease in genes expression of Bax and caspase-2, suggesting that the virus inhibited the process of programmed cell death in bovine embryos seven days post-fertilization, in order to promote viral spread